Sexual behavior among unmarried business process outsourcing employees in Chennai: Gender differences and correlates associated with It - Bimal Charles; Saumya Rastogi; Asirvatham Edwin Sam; Joseph D Williams; Aarthi Kandasamy (Wolters Kluwer Medknow Publications, 2013)
Background: Premarital sex is often associated with high risk sexual behavior such as early age of initiation, multiple partners and inconsistent condom use. Evidence shows that such sexual behavior pre-disposes to sexually transmitted diseases including HIV. Objectives: This paper tried to investigate the correlates of premarital sexual behavior among male and female business process outsourcing (BPO) employees to highlight the gender differences that exist in relation to it. Materials and Methods: Data were collected from 526 unmarried BPO employees during behavioral surveillance survey in Chennai, in the year 2009. Results: The results showed that about one-third of respondents (males - 39.6%, females - 26.1%) had experienced premarital sex. Men reported having had their first sexual intercourse at 12 years and women at 16 years of age. While the prevalence of premarital sex was found to be high, the percentage using a condom during last sex was also high, especially, among the female employees (82.4%). Logistic regression showed that monthly individual income, work in shifts, migration, peer influence and friends with previous sexual experience were significant predictors of premarital sex among the male BPO employees. Visit to night clubs was significantly associated with a higher prevalence of premarital sex among the female employees. Conclusions: The study concludes that there is a significant gender dimension in the premarital sexual behavior among the BPO employees and that even as the sexual behavior of the young people is transitioning; their ability to negotiate safe sex behavior is also increasing. It is recommended to enhance efforts to advocate safe sex behavior among young adults employed in the BPO industry.